Risk management committee and financial instrument disclosure - Mohamat Sabri Hassan,; Norman Mohd Saleh,; Puan Yatim,; Mara Ridhuan Che Abdul Rahman, (FEP, 2012)
In this paper, we empirically investigate the influence of several characteristics of firms on the extent to which Malaysian listed companies disclosed financial instruments during the voluntary and mandatory periods of MASB 24 (Financial Instruments: Disclosure and Presentation) Standard. Following prior studies, we predict that larger and more profitable firms are more likely to disclose more information on financial instruments. We also hypothesize that strong internal control mechanisms, such as the existence of a risk management committee and audit quality, also result in higher levels of disclosure. The sample consists of firms that were listed with the Main Board of Bursa Malaysia in 1999, 2000, 2002, and 2003. This study employs a multiple regression analysis over 484 firm-years. Our results indicate that, on average, the disclosure quality among Malaysian firms is low before the period of mandatory disclosure. However, the level of disclosure appears to increase immediately after the issuance of the MASB 24. We also find that the existence of a risk management committee, firm size and leverage are positively associated with the disclosure quality of financial instruments. Finally, in general, the results indicate that the implementation of financial instrument disclosure standards influence firms, to some extent, to provide high-quality reporting.